A DFT study on multivalent cation-exchanged Y zeolites as potential selective adsorbent for H2S - Sung, Chun-Yi; Al Hashimi, Sale; McCormick, Alon; Cococcioni, Matteo; Tsapatsis, Michael (Microporous and mesoporous materials, 2013)
[Display omitted] ► The potential use of Zn-, Ni-, and Ga-Y as selective adsorbents for H2S was studied. ► The adsorption energies of H2S, CO, H2O, N2, and CO2 on Y cluster were computed. ► Multivalent cation-exchanged zeolites are subject to strong adsorption of water. ► GaY has the largest adsorption selectivity between H2S and CO among all we studied. The potential use of multivalent-cation-exchanged Y zeolites as selective adsorbents for hydrogen sulfide (H2S) from Claus process tail gas was examined; previous work suggested Zn(II)Y, Ni(II)Y, and Ga(III)Y were chosen as representative candidates. The adsorption energies of H2S and other Claus tail gas components (CO, H2O, N2, and CO2) were computed on zeolite cluster models with density functional theory (DFT). It was found that these multivalent cation-exchanged zeolites are subject to strong adsorption of water. The trend in adsorption energy does not change with the cation type and Al distribution, and is similar to that on alkali metal exchanged zeolites found in our previous study. However, the reason for water selectivity is different for the multivalents than for the alkali metal Y’s, and this is revealed by absolutely localized molecular orbital energy decomposition analysis (ALMO EDA). The difference between the adsorption energies of CO and H2S on GaY is the largest among all the cation-exchanged Y zeolites we have studied so far. Therefore, a two-step process, where the H2S adsorption follows the removal of H2O, might be a good strategy for adsorptive desulfurization.